2021
DOI: 10.1021/acs.jmedchem.1c00315
|View full text |Cite
|
Sign up to set email alerts
|

Double Arylation of the Indole Side Chain of Tri- and Tetrapodal Tryptophan Derivatives Renders Highly Potent HIV-1 and EV-A71 Entry Inhibitors

Abstract: We have recently described a new generation of potent human immunodeficiency virus (HIV) and EV-A71 entry inhibitors. The prototypes contain three or four tryptophan (Trp) residues bearing an isophthalic acid moiety at the C2 position of each side-chain indole ring. This work is now extended by both shifting the position of the isophthalic acid to C7 and synthesizing doubly arylated C2/C7 derivatives. The most potent derivative (50% effective concentration (EC 50 ) HIV-1, 6 nM; EC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Visual inspection of the models previously generated for AL-471 bound to the fivefold axis of the EV-A71 capsid protein VP1 [ 22 ] suggests that replacement of l -Trp units with d -Trp would generate similar binding modes for 6 ( Supporting Information ). With respect to HIV, the detailed models reporting the interaction of a membrane-embedded and heavily glycosylated HIV-1 Env trimer with the doubly arylated tetrapodal derivative AL-518 —previously described by our group [ 35 ]—revealed preferential binding to a location close to the V3 loop of gp120 that can be similarly targeted by the new 23 ( AL-534 ). Subtle differences in potency against HIV-1 and HIV-2 for 23 ( AL-534 ) are to be expected due to (i) well-known sequence and loop differences between HIV-1 and HIV-2, (ii) the multiple patterns of simultaneous CH···π stacking and hydrogen-bonding interactions that are possible between the distinct isophthalic acid-decorated Trp units and the oligomannose glycans attached to Asn residues at positions 134, 197, and 363 in HIV-1, (iii) modulation of electrostatic interactions with the side-chain guanidinium moieties of Arg151 (conserved in HIV-2) and Arg469 (Thr481 in HIV-2) [ 35 ], and (iv) the fact that antibodies do not usually cross-react between HIV-1 and HIV-2.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Visual inspection of the models previously generated for AL-471 bound to the fivefold axis of the EV-A71 capsid protein VP1 [ 22 ] suggests that replacement of l -Trp units with d -Trp would generate similar binding modes for 6 ( Supporting Information ). With respect to HIV, the detailed models reporting the interaction of a membrane-embedded and heavily glycosylated HIV-1 Env trimer with the doubly arylated tetrapodal derivative AL-518 —previously described by our group [ 35 ]—revealed preferential binding to a location close to the V3 loop of gp120 that can be similarly targeted by the new 23 ( AL-534 ). Subtle differences in potency against HIV-1 and HIV-2 for 23 ( AL-534 ) are to be expected due to (i) well-known sequence and loop differences between HIV-1 and HIV-2, (ii) the multiple patterns of simultaneous CH···π stacking and hydrogen-bonding interactions that are possible between the distinct isophthalic acid-decorated Trp units and the oligomannose glycans attached to Asn residues at positions 134, 197, and 363 in HIV-1, (iii) modulation of electrostatic interactions with the side-chain guanidinium moieties of Arg151 (conserved in HIV-2) and Arg469 (Thr481 in HIV-2) [ 35 ], and (iv) the fact that antibodies do not usually cross-react between HIV-1 and HIV-2.…”
Section: Resultsmentioning
confidence: 93%
“…With respect to HIV, the detailed models reporting the interaction of a membrane-embedded and heavily glycosylated HIV-1 Env trimer with the doubly arylated tetrapodal derivative AL-518 —previously described by our group [ 35 ]—revealed preferential binding to a location close to the V3 loop of gp120 that can be similarly targeted by the new 23 ( AL-534 ). Subtle differences in potency against HIV-1 and HIV-2 for 23 ( AL-534 ) are to be expected due to (i) well-known sequence and loop differences between HIV-1 and HIV-2, (ii) the multiple patterns of simultaneous CH···π stacking and hydrogen-bonding interactions that are possible between the distinct isophthalic acid-decorated Trp units and the oligomannose glycans attached to Asn residues at positions 134, 197, and 363 in HIV-1, (iii) modulation of electrostatic interactions with the side-chain guanidinium moieties of Arg151 (conserved in HIV-2) and Arg469 (Thr481 in HIV-2) [ 35 ], and (iv) the fact that antibodies do not usually cross-react between HIV-1 and HIV-2. Studying this variation in depth is further complicated by the fact that Env proteins gp120 and gp41 subunits in the different HIV-1/HIV-2 subtypes or clades exist as populations of glycosylated variants (glycoforms) that are characterized by heterogeneous patches of oligomannose-type glycans at each N-linked glycosylation site.…”
Section: Resultsmentioning
confidence: 93%
“…Prior work from our group has shown multivalent functionalized tryptophan (Trp) derivatives to be potent inhibitors of different viruses, including human immunodeficiency virus (HIV), enterovirus 71 (EV-A71), and flavivirus infections, and to show low cytotoxicity. Mechanistic studies demonstrated that these compounds interact with key elements of the viral surface (glycoprotein gp120 of HIV, 5-fold axis of the EV-A71 capsid and domain III of the viral envelope glycoprotein dengue 2 virus) preventing virus attachment to the host cell membranes. In previous studies, the existence of carboxylates at the Trps was shown to be critical for antiviral activity.…”
Section: Introductionmentioning
confidence: 99%